Effect of HIV/AIDS education on changing students' sexual practices in secondary schools in Temeke Municipality, Tanzania - Zuhura R. Said; Prospery M. Mwila (Action Research Journal Indonesia (ARJI), 2025)
This study aimed to assess the effect of HIV/AIDS education on changing students' sexual practices in secondary schools in Temeke Municipality. The objectives were to assess the general awareness of students on HIV/AIDS in Temeke Municipality, to identify the sources of information on HIV/AIDS among secondary school students in Temeke Municipally and to determine the role of HIV/AIDS awareness in changing students’ sexual practices in secondary schools in Temeke Municipality. The study employed the Health Belief Model and Planned Behavioural Theory. The study used a mixed-method approach in data collection. The data were collected by conducting interviews with teachers and parents, documentary reviews, and questionnaires for students and teachers from public secondary schools in Temeke Municipality. Data were analysed by descriptive statistical analysis and presented in tables and graphs. The findings of this study revealed that most students are aware of HIV/AIDS. Some of them were able to write the long form of HIV/AID, while others failed to do so. The major source of HIV/AIDS education in visited secondary schools in Temeke municipality was the subjects of civics and biology. In these two subjects, the students are taught the causes, symptoms, effects and precautions for avoiding the spread of HIV/AIDS. The study further revealed that there is no great change among visited students in secondary schools in Temeke municipality. The students were observed to misbehave to the extent of being expelled from their studies. Most of the visited students engaged in sexual relations at an early age. The study concluded that awareness campaigns should be designed at school levels to prevent and protect adolescents from HIV/AIDS and to spread awareness to induce behavioural change among adolescents.